THE PATHWAYS OF WOMEN EMPOWERMENT THROUGH SHG FEDERATIONS – A STUDY WITH REFERENCE TO RURAL TELANGANA - Janaki, T. (PEOPLE: International Journal of Social Sciences, 2015)
Social development is emerging as a very important sector alongside Information Technology. Scholars like Amartya Sen. have focused on social development and elaborately dealt of how education, health and environment are very essential for survival and development of Human kind. Women Empowerment occupies pivotal place as a tool for social and human development. Many state governments in India since IX plan identified model of SHG Bank linkage program as ‘best fit’ for women empowerment. SHG federation model is an improved model of micro finance which is run under the name Indira Kranthi Patham in the study area – Range Reddy district of Telangana. However, changing times also observe the ‘melt down’ of high expectations about the transformational effects of micro finance. Several doubts are raised on genuineness of gender equity that is brought by mere financial help. It is now widely felt that a further probe is necessary about the process of empowerment that exactly takes place. The present study is an attempt to study the impact of that program on SHG member – loan beneficiaries. Respondents are divided into two categories namely micro entrepreneurs and passive beneficiaries and the path of empowerment for both these groups is identified. Multi group analysis is done along with the study of pair wise parameters for assessing the statistical significance of difference in paths. Major finding of the study is the variation in the paths of empowerment of both categories.